‘Minor’ educator before Comenius: Petr Chelčický’s pacifism - Thiago Borges de Aguiar (Acta Scientiarum. Education, 2015)
This paper deals with Petr Chelčický, who lived in Bohemia in the first half of the fifteenth century. In the exercise of historiographical look over the place given to this person in the history of religions, the text proposes re (build) his place in the history of education using the category of ‘minor’ educator. This category binds to the historiographical movement of studying smaller authors and proposes another look at how we research and teach the history of education. For the case study in this article, we start from the contextualization of the Hussite movement in the Czech lands, with a ransom of some little-known names. It follows with analysis of Chelčický’s image, his influences and writings, especially his work The net of true faith, redeeming aspects of pacifism and opposition to the tripartite division of society. At the end of the text, it approaches Chelčický's ideas with Jan Amos Comenius, the ‘great’ educator who is consecrated by the history of education.